The Influence of Positive Manager Feedback and Performance Appraisal in The Innovative Behavior of PT. Evertech International Group Employees - Azizah Sarah; Sabrina, Nina Novi; Suzana, Anna (Mabsya: Jurnal Manajemen Bisnis Syariah, 2025)
The increase in innovation in the manufacturing sector is driven by rapid technological advances and increasingly complex industrial competition. To answer these challenges, this study aims to analyze the effect of positive feedback from managers and performance appraisals on employee innovative behavior at PT Evertech International Group, a manufacturing company in Brebes, Central Java. This study uses a quantitative approach with a census method involving 150 respondents. Data were collected through a questionnaire with a Likert scale and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS 4.1.0.9. The analysis process includes measuring convergent and discriminant validity, as well as testing the reliability of constructs and hypotheses. The results show that positive feedback from managers and performance appraisals have a significant and positive impact on employee innovative behavior. The path coefficients for manager feedback and performance appraisals are 0.396 and 0.444, respectively, both with a p-value of 0.000, indicating a statistically significant effect.  Further analysis revealed that employees were more motivated to generate innovative ideas when they received constructive and consistent feedback and when innovation was included in performance evaluations. The combined effect of the two variables explained 59.1% of the variance in innovative behavior, reflecting a strong synergistic effect. The discussion highlights the role of a supportive work environment and an innovation-oriented appraisal system in fostering creative thinking. In conclusion, companies should empower managers with effective communication skills and develop performance systems that reward creativity.